Expression of TERT in precancerous gastric lesions compared to gastric cancer - Duarte, M. C. [UNESP]; Babeto, Erica [UNESP]; Leite, K. R. M.; Miyazaki, K.; Borim, A. A.; Rahal, Paula [UNESP]; Silva, A. E. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2011)
The objective of this study was to determine the levels of TERT mRNA and TERT protein expression in stomach precancerous lesions such as intestinal metaplasia (IM) and gastric ulcer (GU) and compare them to gastric cancer (GC). Real-time PCR was performed to detect TERT mRNA expression levels in 35 biopsies of IM, 30 of GU, and 22 of GC and their respective normal mucosas. TERT protein was detected by immunohistochemistry in 68 samples, 34 of IM, 23 of GU, and 11 of GC. Increased TERT mRNA expression levels were observed in a significant number of cases, i.e., 46% of IM, 50% of GU, and 79% of GC. The relative mean level of TERT mRNA after normalization with the β-actin reference gene and comparison with the respective adjacent normal mucosa was slightly increased in the IM and GU groups, 2.008 ± 2.605 and 2.730 ± 4.120, respectively, but high TERT mRNA expression was observed in the GC group (17.271 ± 33.852). However, there were no statistically significant differences between the three groups. TERT protein-positive immunostaining was observed in 38% of IM, 39% of GU, and 55% of GC. No association of TERT mRNA and protein expression with Helicobacter pylori infection or other clinicopathological variables was demonstrable, except for the incomplete type vs the complete type of IM. This study confirms previous data of the high expression of both TERT mRNA and protein in gastric cancer and also demonstrates this type of changed expression in IM and GU, thus suggesting that TERT expression may be deregulated in precursor lesions that participate in the early stages of gastric carcinogenesis.
Keywords: Gastric ulcer; Intestinal metaplasia; Gastric cancer; TERT; Gene expression; Protein expression